Spinal dysraphism with tripedus morphology: A case report - Monis, Mohd; Wahab, Shagufta; Koppal, Divyashree; Ibbrahim, Aiman (Indian Journal of Case Reports, 2021)
This is a rare case report of a 5-month-old child with a complex spinal dysraphic state, and an accessory limb (tripedus morphology), accessory genitalia, and anal dimple. The child was brought to the hospital with an accessory limb arising from the back. On clinical examination, an accessory limb arising from the lower back with a partially developed foot with the presence of toes and nails was noted. Spinal MRI was advised which revealed dysraphic features including spina bifida with the low lying and posteriorly tethered cord with diastematomyelia along with a supernumerary appendage attached to the vertebral column having rudimentary bones resembling those of extremities. The presence of an accessory limb with spinal dysraphism is quite a rare anomaly. The condition can be treated by surgical intervention and involves excision of the accessory limb with adequate dural and paraspinal muscle cover.